Peningkatan Literasi Bahasa Inggris Anak Melalui Pembacaan Buku Cerita Bergambar di Rumah Belajar “Jadi Mulya Bersama” (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
The English Fun Tales program is a community service activity aimed at improving children's English literacy through the use of picture books. This activity was carried out at Rumah Belajar Jadi Mulya, Salatiga, which serves as a non-formal learning center for children from the surrounding area. The background of this program stems from the limited access of children in the area to attractive, interactive, and developmentally appropriate English learning resources. The implementation method includes: (1) providing English picture books selected according to the children's language ability and age; (2) guided shared reading activities; (3) simple discussions about story content to train comprehension; and (4) creative activities such as drawing story characters, role-playing, or story retelling. This approach is designed to combine cognitive, affective, and psychomotor aspects, so that children not only understand vocabulary and language structure but also develop imagination, self-confidence, and reading interest. The implementation results show an increase in reading interest, expansion of English vocabulary, and children's courage in expressing themselves orally. In addition, social interaction among participants becomes more positive through collaborative activities. This program is expected to serve as a model for English literacy learning based on picture books that can be replicated in other learning communities with local context adjustments.